Design and fabrication of waste compactor trash can / Wan Syafiq Nadzmie Wan Suhaimi - Wan Suhaimi, Wan Syafiq Nadzmie (2023)
Dustbin is a common product that people often use in their daily life. It is a place for rubbish, so that people can throw into it. Hence, when the dustbin is full, the user must clean their plastic rubbish and replace with a new plastic. The problem occurred is that people did not use the space in the dustbin to the fullest that make the waste in the trash always spill and overflow. Because of that reason, it is necessary to make a dustbin that can compact all the waste that contained in the rubbish so we can use all the space left in the dustbin completely. The objective of doing this project is to analyses and design a waste compactor dustbin so and fabricate a waste compactor trash can. The expected result is that the product can work functionally to compact all the waste in the dustbin. In a nutshell, this project can help people to ease their routine in their daily life